Teknologi Irigasi Berbasis IoT: Integrasi Sensor Nirkabel (SN), Energi Surya dan Logika Fuzzy - Sahibu, Supriadi; Surahman; Ahmad, Andani (Unversitas Muhammadiyah Riau, 2025)
Agriculture is a vital sector in the global economy that faces various challenges, especially in the efficient use of water resources. Irrigation is an important aspect of agriculture, especially in rice fields, because optimal water supply directly affects plant productivity. However, in Pao Village, Malangke District, and North Luwu Regency, water availability is increasingly limited due to climate change, urbanization, and inefficient exploitation of resources. Most farmers in the area do not have irrigation networks so during the dry season their rice fields experience drought and are at risk of crop failure. This study aims to design and develop an automatic irrigation system based on the Internet of Things (IoT) supported by wireless sensors and solar energy to improve the efficiency of water use in rice fields. The research method used is a prototype approach consisting of three main stages, namely preparation, prototype development, and system implementation. In the preparation stage, field observations and literature studies were carried out to determine system needs. The development stage includes design, implementation, and internal evaluation of the prototype. Furthermore, the system was implemented and tested in the field to assess its effectiveness in controlling irrigation automatically. The results of the study showed that the developed system was able to detect water levels using ultrasonic sensors and humidity sensors connected to Arduino. Data from the sensors is processed using fuzzy logic to automatically control the water pump based on the water conditions in the farmland. The energy used comes from solar panels, so the system can operate independently and is environmentally friendly. Tests have shown that the system works well in regulating the water supply to the rice fields efficiently and can help farmers overcome drought and increase agricultural productivity.